2017
DOI: 10.1186/s40795-017-0157-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in diet quality during a 12 month weight loss randomised controlled trial

Abstract: Background: Reductions in energy intake are seen in weight loss trials, but whether this occurs with improvements to diet quality (DQ) is less established. The aim of this study was to evaluate changes in diet quality in a sample of volunteers in a weight loss trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 95 publications
(131 reference statements)
0
9
0
Order By: Relevance
“…A clinical trial that provided participants with walnuts reported improvements in overall dietary quality ( 58 ). Previous research has also suggested that the provision of walnuts in the context of healthy eating advice resulted in significant increases in the quality of the overall diet patterns ( 59 ), with increased fruit consumption and decreased discretionary food consumption reported ( 10 ). Nut consumers may also have higher intakes of vegetables ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial that provided participants with walnuts reported improvements in overall dietary quality ( 58 ). Previous research has also suggested that the provision of walnuts in the context of healthy eating advice resulted in significant increases in the quality of the overall diet patterns ( 59 ), with increased fruit consumption and decreased discretionary food consumption reported ( 10 ). Nut consumers may also have higher intakes of vegetables ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…43 However, the SFA and weight show no significant reduction in this study, probably due to the type of the whole food consumed was generally the same with some changes based on their dietary assessment. 44 During the study period, reducing salt intake (e.g., soy sauce, added salt in the cooking, flavour enhancers) was one of the main components in the lifestyle modification intervention. The recommendation was to limit salt intake to 5 g per day (3 mg sodium).…”
Section: Discussionmentioning
confidence: 99%
“… 43 However, the SFA and weight show no significant reduction in this study, probably due to the type of the whole food consumed was generally the same with some changes based on their dietary assessment. 44 …”
Section: Discussionmentioning
confidence: 99%
“…Median intakes at 3 months showed a similar shortfall to that of the average Australian adults consumption patterns ( 11 ) . Because HealthTrack was primarily a weight loss intervention, the significant reduction in total energy intakes over 3 months ( 13 ) could have reflected intakes of these two food groups, even taking reductions in discretionary food consumption into account ( 21,22 ) . Furthermore, previous research from this team has shown that rather than switching to a higher quality dairy products male participants opted to eliminate them completely ( 23 ) .…”
Section: Discussionmentioning
confidence: 99%